2019
DOI: 10.1016/j.celrep.2019.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Driving Neuronal Differentiation through Reversal of an ERK1/2-miR-124-SOX9 Axis Abrogates Glioblastoma Aggressiveness

Abstract: Highlights d Stem cell-derived glioma formation is accompanied by loss of neurogenesis d miR-124-dependent neuronal differentiation reduces glioblastoma (GBM) aggressiveness d An ERK1/2-miR-124-SOX9 axis regulates neuronal differentiation in GBM cells d An miR-124-induced neuronal phenotype sensitizes GBM cells to radiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 94 publications
2
25
0
Order By: Relevance
“…In the central nervous system, Sox9 plays an important role in the differentiation of cranial neural crest cells (8), and was reported as an astrocyte-specific nuclear marker in adult brain outside the neurogenic regions (33). We found here that Sox9 was overexpressed in clinical gliomas, and correlated with a poor prognosis of glioma patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the central nervous system, Sox9 plays an important role in the differentiation of cranial neural crest cells (8), and was reported as an astrocyte-specific nuclear marker in adult brain outside the neurogenic regions (33). We found here that Sox9 was overexpressed in clinical gliomas, and correlated with a poor prognosis of glioma patients.…”
Section: Discussionsupporting
confidence: 57%
“…Genetic mutation is known to drive malignant transformation at least in part by "hijacking" neurodevelopmental programs (4,5). Increasing evidence has suggested that Sox9, an indispensable transcription factor in the development of the nervous system, plays a pivotal role in the pathogenesis of glioma (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…TRIzol solution was used for total RNA extraction from cells and harvested tissues. Cycling conditions were set as previously mentioned, 19 and the genes expression was normalized to ARF5 and U6. A melting curve confirmed the specificity of the amplification products.…”
Section: Methodsmentioning
confidence: 99%
“…[1440] MicroRNA also acts as a regulator for neurogenesis. [4142] Possibly, the identification of some exosomal cargoes[43] might be an easier task compared to the identification of the soluble proteins and lipids present in the EPC-CM.…”
Section: Endothelial Progenitor Cell-derived Conditioned Medium Incrementioning
confidence: 99%